Sex-related differences in plaque characteristics and endothelial shear stress related plaque-progression in human coronary arteries. (February 2022) - Wentzel, Jolanda J.; Papafaklis, Michail I.; Antoniadis, Antonios P.; Takahashi, Saeko; Cefalo, Nicholas V.; Cormier, Michelle; Saito, Shigeru; Coskun, Ahmet U.; Stone, Peter H.
Abstract: Background and aims: Clinical atherosclerosis manifestations are different in women compared to men. Since endothelial shear stress (ESS) is known to play a critical role in coronary atherosclerosis development, we investigated differences in anatomical characteristics and endothelial shear stress (ESS)–related plaque growth in human coronary arteries in men compared to women. Methods: 1183 coronary arteries (male/female: 944/239) from the PREDICTION study were studied for differences in artery/plaque and ESS characteristics, and ESS-related plaque progression (6–10 months follow-up) among men and women and after stratification for age. All characteristics were derived from IVUS-based vascular profiling and reported per 3 mm-segments (13, 030 3-mm-segments (male/female: 10, 465/2, 565)). Results: Coronary arteries and plaques were significantly smaller in females compared to males; but no important differences were observed in plaque burden, ESS and rate of plaque progression. Change in plaque burden was inversely related to ESS ( p< 0.001) with no difference between women versus men (β: -0.62 ± 0.13 vs −0.68 ± 0.05, p= 0.62). However, stratification for age demonstrated that ESS-related plaque growth was more marked in young women compared to men (<55 years, β: −2.02 ± 0.61 vs −0.33 ± 0.10, p= 0.007), reducing in magnitude over the age-categories up till 75 years. Conclusions: Coronary artery and plaque size are smaller in women compared to men, but ESS and ESS- related plaque progression were similar. Sex-related differences in ESS-related plaque growth were evident after stratification for age. These observations suggest that although the fundamental processes of atherosclerosis progression are similar in men versus women, plaque progression may be influenced by age within gender. Graphical abstract: Image 1 Highlights: Coronary arteries from women are smaller and contain smaller plaques compared to men. Shear stress-related plaque growth in women is different from men dependent on age. Women demonstrate changes in endothelial shear stress (ESS) -related plaque growth with progressive age. Pathophysiology of atherosclerosis progression might be influenced by the gender and age of the patient.